Fuzzy Logic-Based Aquaculture Climate Control System Design On A Fishpond - Damar Wicaksono; Affix Mareta; Beta Estri Adiana; D Jayus Nor Salim (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
One important key to determining water quality as a habitat for live fish is the climate of the water. A good water climate in aquaculture is needed by aquatic animals to survive, such as fish and other aquatic organisms. To maintain it, it can be controlled by the aeration rate and monitoring the amount of water by microcontroller. Monitoring water quality and maintaining the amount of water activity at a certain volume is necessary by farmers to get good harvests. Fish Farmers typically rely on irrigation and rain, which cause the aquatic climate to change. Therefore, this research proposed to design a system to maintain the water climate and amount of water so that they remain in accordance with the levels required by fish. In general, a water climate control system using Mamdani fuzzy logic control has been implemented, which is used to manipulate output equipment in the form of aeration speed based on water climate parameters as the input. This system will also automatically control to drain or refill water if needed by water pump. This system consists of materials, components, and sensors to get the data. A pond-type aquarium is used as a simple test. As a method to make this happen, fuzzy logic is used based on the available input and categorizes it into several criteria, then provides knowledge-based principles, inference mechanisms, and the defuzzification phase. The test results showed success in controlling the water climate quality and the maintain amount of water, with success rate at 88,89% and 91,67%. This shows that the proposed system has worked effectively to control climate water quality and maintain the amount of available water.